The Effect of Career Development, Competence And Compensation of Intention To Leave Employees In Ekasakti University of Padang - Fajra, Melda; Novalinda, Rina; Giatman, M.; Syahril, Syahril (International Journal for Educational and Vocational Studies, 2020)
The purpose of this study was to determine the effect of career development, competence and compensation on intention to leave Employees at Ekasakti University, Padang. The research method uses correlational analysis. The sampling technique uses a purpose sampling method, amounting to as many as 30 people. Data collection techniques using questionnaires using a Likert scale. Data analysis techniques using data description, normality test and hypothesis testing using SPSS Version 21. The results of the study illustrate that simultaneously there is an influence jointly with career development, competence and compensation for Intention To Leave, and testing conducted partially, that the development career influences Intention To Leave, competence influences Intention To Leave and compensation influences Intention To Leave.